Problems with a recent genome-wide association study in schizophrenia. Issue 2 (3rd April 2018) - Ross, Colin A.; Ross, Andrew W.
ABSTRACT: A recent study of the frequency of schizophrenia in 22q11.2 deletion syndrome illustrates the serious problems with genome-wide association studies in schizophrenia. In an editorial accompanying the paper in The American Journal of Psychiatry, it is stated that this deletion occurs in only 0.3% of cases of schizophrenia, and yet it is said to be one of the strongest genetic risk factors for schizophrenia identified to date. Perhaps it is time to consider whether further investment in genome-wide association studies in schizophrenia is worthwhile, and whether they have even a tiny likelihood of yielding clinically useful results.